Evaluation of CHIKPGRO model in semi arid and sub-humid climatic conditions of Madhya Pradesh - SILAWAT, SANDIP; AGRAWAL, K. K.; SRIVASTAVA, A. K. (MAUSAM, 2016)
Based on field experiments conducted under different thermal and moisture regimes during rabi 2009-10 and 2010-11 at Jabalpur and Tikamgarh district of Madhya Pradesh, CHIKPGRO model was calibrated and validated for two popular and widely grown chickpea cultivars (JG 315 and JG11). Validations were done on the crop grown under the six dates of sowing in 2010-11 at Jabalpur (irrigated) and under two dates of sowing (2009-10 and 2010-11) at Tikamgarh (rainfed). The model overestimated the major phenological events under irrigated and underestimated in rainfed conditions, except the physiological maturity. The model also overestimated maximum LAI, biomass, seed yield and unit seed weight under irrigated conditions and underestimated in rainfed, conditions. The validation error was higher in rainfed conditions than irrigated conditions. The model simulated cultivars yield and biomass in irrigated and rainfed conditions differently with same genetic coefficients. The model simulated higher thermal and moisture stress than the actual field conditions under late sown conditions. The cultivar JG 11 had shown slightly more difference in simulation of yield and biomass as compared to JG 315. The model performance was tested with help CRM, RMSE and percentage difference between observed and simulated values.